MODAL KANDIDAT GUS IPUL DALAM PEMILIHAN GUBERNUR JAWA TIMUR 2018 - Ayodya, Beta Puspitaning (representamen, 2018)
Simultaneous elections will be held in Indonesia in 2018, one of which is theGovernor Election (Pilgub) of East Java to replace Pak Karwo and Gus Ipul. Candidateswho will compete in this East Java Pilgub are Gus Ipul (as incumbent), and Khofifah(formerly a social minister). Both candidates are both from the largest mass organization inEast Java, namely Nahdltul Ulama (NU). In relation to this background, the author wouldlike to examine about how Gus Ipul's political capital and strategy of communication in EastJava Pilgub 2018. This study uses case study because want to answer about how (how) in theformulation of research. By using different political communication strategies, of course theresults achieved by both candidates will be different. Gus Ipul used a defensive strategy tomaintain his position as an incumbent. By using his capital-capital (economic, social,cultural and symbolic) conversion, Gus Ipul seeks to mobilize the masses, most of whom areNU citizens. Conversion of existing capital into a political capital, allowing Gus Ipul toachieve victory in this 2018 East Java Pilgub.Keywords: capital, political strategy